Soil health and ecological risk assessment in the typical coal mines on the Mongolian Plateau. (September 2022) - Kou, Jin; Gan, Yuchen; Lei, Shaogang; Meng, Wei; Feng, Chao; Xiao, Hongxing
Graphical abstract: Abstract: Mining activities always lead to severe soil pollution and vegetation degradation. However, the assessment of soil pollution and ecological risk due to mining has not been applied on the Mongolian Plateau, which has plenty of typical coalmines with environmental heterogeneity. Soil samples were collected from the Shengli Mine and the Baorixile Mine in Inner Mongolia to compare soil physicochemical properties and concentrations of metals/metalloids in locations with climate and precipitation differences. The single-factor pollution, Nemerow composite, geo-accumulation and potential ecological risk indices were used to investigate the environmental risks from two mines. The results show that the soils of these two mining areas have the characteristics of high pH (close to 8.5), high sand ratio and low nutrient content, and the soil texture was classified as sandy soil. Cu, Pb, Zn, Mn, Ni, As and Hg in the two mines all exceeded the average soil background values. Furthermore, the two mining areas have differences in the soil environment, including a higher C/N ratio and sand content in the Shengli Mine while having significantly higher As and Pb contents in the Baorixile Mine. In addition, pollution indices indicated that the soil of the Baorixile Mine poses a higher ecological risk even though it has higher nutrients and better soil structure than Shengli Mine does. In summary, coal mining is the key driver that leads to the ecological risk of the two mines, and the environment with relatively higher vegetation abundance and more suitable climatic conditions could have a higher ecological risk due to the comprehensive factors of climate and human interference. This study helps to clarify the ecological risks of soil metals, determine the priority control components of contaminated soil and prioritise appropriate protection measures and monitoring plans for the Inner Mongolian Plateau.